The Use of Comparative Genomic Analysis for the Development of Subspecies-Specific PCR Assays for Mycobacterium abscessus - Akwani, Winifred C.; van Vliet, Arnoud H.M.; Joel, Jordan O.; Andres, Sönke; Diricks, Margo; Maurer, Florian P.; Chambers, Mark A.; Hingley-Wilson, Suzanne M. (Frontiers in Cellular and Infection Microbiology, 2022)
Mycobacterium abscessus (MABC) is an important pathogen of immunocompromised patients. Accurate and rapid determination of MABC at the subspecies level is vital for optimal antibiotic therapy. Here we have used comparative genomics to design MABC subspecies-specific PCR assays. Analysis of single nucleotide polymorphisms and core genome multilocus sequence typing showed clustering of genomes into three distinct clusters representing the MABC subspecies M. abscessus, M. bolletii and M. massiliense. Pangenome analysis of 318 MABC genomes from the three subspecies allowed for the identification of 15 MABC subspecies-specific genes. In silico testing of primer sets against 1,663 publicly available MABC genomes and 66 other closely related Mycobacterium genomes showed that all assays had >97% sensitivity and >98% specificity. Subsequent experimental validation of two subspecies-specific genes each showed the PCR assays worked well in individual and multiplex format with no false-positivity with 5 other mycobacteria of clinical importance. In conclusion, we have developed a rapid, accurate, multiplex PCR-assay for discriminating MABC subspecies that could improve their detection, diagnosis and inform correct treatment choice.